Simulation of hybrid systems from natural language requirements - OLIVEIRA, Bruno Medeiros de (2016)
Despite technological advances in the industry of systems development, testing is still the most commonly used verification method to ensure reliability. Model-based testing (MBT) techniques are principally employed for the purpose of generating test cases from specification models. Contributing to this branch of research an MBT strategy for creating test cases from controlled natural language (CNL) requirements was created, called NATural Language Requirements to TEST Cases (NAT2TEST). The NAT2TEST strategy deals with data-flow reactive systems, a class of embedded systems whose the main feature is to have the inputs and outputs always available as signals. However, there is a demand from the industry to to apply the strategy in the context of hybrid systems. These systems are a fusion of continuous dynamical and discrete dynamical systems, that is, they combine dynamical characteristics from both continuous and discrete worlds. Hybrid systems have received much attention in the last years. The main contribution of this work is to extend the NAT2TEST strategy to deal with hybrid systems. Using the new proposed approach, it is possible to write the requirements of a hybrid system, whose semantics is characterised based on the case grammar theory. Then, a formal representation of the system is built considering a model of hybrid data-flow reactive systems. Finally, to analyse the system behaviour via simulation, a modelling environment for simulation of hybrid systems was used, called Acumen. Thereby, a specification model in Acumen is generated and simulated in this environment. The characteristics of the new approach are exemplified using two examples, one belonging to the electronic field, the DC-DC Boost Converter (BC), and the other belonging to the automotive domain, the Adaptive Cruise Control (ACC).